Shading effects of intercropping roselle (Hibiscus sabdariffa) genotypes on plant development, assimilate partitioning and leaf nutrient content (International Journal of Agricultural Research, Innovation and Technology, 2018)
An experiment was conducted to determine the effects of shade on plant development, macronutrient and secondary metabolites in roselle (Hibiscus sabdariffa). Three roselle accessions (ZM 5729, ZM 5738 and ZM ZM5748) acquired from the Zambia National Plant Genetic Resource Centre were used and shade was imposed by intercropping roselle with maize (Zea mays). A Split plot design with shade as main plot and genotype as split- plot was used. Nutritional and development parameters were monitored. At 14 weeks shaded plants had about a three-fold decrease in branches numbers compared to unshaded ones. Plant height was higher in unshaded treatments (120 cm) compared to shaded (83 cm). Plant height of ZM 5738 was significantly higher than the other two accessions. Shading reduced dry matter accumulation by almost 75 % across genotypes with about 20 g per plant in shaded treatments and 73 g in unshaded treatments. Nutrient reductions were highest in fat (60.6 %), fibre (48.4 %), protein (37.8 %), and lowest in ash (27.3 %). In terms of strength of partitioning the pattern was: branches ˃ leaves ˃ roots ˃ squares ˃ flowers. The carbohydrate content increased with shading (10.6 %). Vitamin C content was higher in unshaded treatments in comparison with shaded conditions. ZM 5738 had the highest content followed by ZM 5748 and ZM 5729 had the least content. Oxalates which are an anti- nutrition factor increased with shade. The findings showed that there is significant variation among genotypes and in future selections can be made to choose the most productive genotypes.Int. J. Agril. Res. Innov. & Tech. 8 (1): 7-13, June, 2018